An Examination of Cinnamon Farmers Entrepreneurial Behaviour in Sri Lankan Context - Sachithra, K.M.V. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2020)
As the oldest and the longest form of economic endeavor, entrepreneurialism has become a key aspect in agricultural sector. As economic changes, the agriculture farmers need to focus on innovation, risk taking and the leadership. This study investigates the entrepreneurial behaviour of farmers, how entrepreneurial behaviour varies in terms of gender, education and experience, the link between entrepreneurial behaviour and farm financial success and the nature of the skills that farmers need to become entrepreneurs in agricultural sectors. The study was carried out with owners who have experience in the commercial cultivation of cinnamon crops in two districts in Sri Lanka. Primary data were collected through a survey using a self-administered structured questionnaire. In addition, qualitative research design was also used to investigate the nature of the skills that farmers need to become entrepreneurs in agricultural sectors. This study revealed a moderate level of entrepreneurial behaviour of the farmers. They have shown their attraction towards risk taking; however, practical issues were there that restricted farmers from change-orientation to utilizing opportunities. Further, there was a statistically significant influence of entrepreneurial behaviour to financial performance of cinnamon crop farms. According to the interviews, the farm owners who showed entrepreneurial behaviour are equipped with the skills of learning by doing, centralised decision-making, targeting and analyzing market trends. The study found that entrepreneurial behaviour seems to have its own characteristics in each context which can be varied in different countries. In this study, it is the combination of individual, behavioural strategies and institutional factors. Accordingly, the study discusses the implications and providing a framework that will encourage to make effort on the complexity of entrepreneurial farmer.
Keywords: Farmer; Entrepreneurial Behaviour; Developing country; Agribusiness, Farm success